Reformasi santunan dan implikasinya terhadap kinerja keuangan PT Jasa Raharja: Tinjauan berdasarkan PMK No. 15 dan 16 Tahun 2017 - Aden Apandi; Siti Almurni; Lina Noersanti; Juniarti Juniarti (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study aims to analyze and determine the financial performance of PT Jasa Raharja before and after the issuance of PMK No. 15-16 / 2017 with the measurement variables of Net Profit Margin (NPM), Return on Assets (ROA) and Current Ratio (CR). The method used is quantitative descriptive. The sample in this study is PT Jasa Raharja. The data used are in the form of annual financial reports for 2014, 2015, 2016, 2018, 2019 and 2020. Data testing uses descriptive statistics with normality tests, and paired sample t-tests. The results of the study indicate that there is a difference in the financial performance of PT Jasa Raharja before and after the issuance of PMK No. 15-16 / 2017 seen from the measurement of Net Profit Margin (NPM) and Return on Assets (ROA), while there is no difference in the financial performance of PT Jasa Raharja before and after the issuance of PMK No. 15-16 / 2017 seen from the measurement of Current Ratio (CR). Public interest statement This study is beneficial to the general public because it shows that despite a decline in financial performance after the enactment of PMK No. 15-16/2017, PT Jasa Raharja is still able to fulfill its obligation to pay compensation. This provides confidence that public services continue to run well and stably. The practical implication is that the government and BUMN can evaluate similar policies so that they remain on the side of the community without disrupting the sustainability of the company's operations.